2005
DOI: 10.1164/rccm.200402-220oc
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Intake in Pregnancy in Relation to Wheeze and Eczema in the First Two Years of Life

Abstract: Two thousand women were recruited for a prospective investigation of the influence of maternal antioxidant intake in pregnancy on the development of asthma and eczema in children. A food frequency questionnaire was used to characterize diet during pregnancy and blood antioxidant levels were measured. Postal questionnaires were used to follow up the 1,924 singleton children born to the cohort at 6, 12, and 24 months of age. There were no associations between maternal antioxidant intake and wheezing symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
211
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(228 citation statements)
references
References 60 publications
(74 reference statements)
8
211
4
5
Order By: Relevance
“…In a study in England, dietary supplementation with a-tocopherol in soy oil to subjects with asthma had no impact on FEV 1 , asthma symptom scores, or bronchodilator use, but in our interpretation, the g-tocopherol in the soy oil may oppose the benefit of the a-tocopherol (43). In a Scottish cohort, reduced maternal intake of vitamin E (likely referring to a-tocopherol) is associated with increased incidence of asthma and wheezing in children up to 5 years old (44,45). In Devereux's review of these data and changes in the environment in Scotland (45), it is discussed that from 1967 to 2004 there was a significant increase in vegetable oil intake by the Scottish, and we suggest that this would at least result in an increase in g-tocopherol, because vegetable oil (soybean oil) is rich in g-tocopherol ( Figure 1C).…”
contrasting
confidence: 47%
“…In a study in England, dietary supplementation with a-tocopherol in soy oil to subjects with asthma had no impact on FEV 1 , asthma symptom scores, or bronchodilator use, but in our interpretation, the g-tocopherol in the soy oil may oppose the benefit of the a-tocopherol (43). In a Scottish cohort, reduced maternal intake of vitamin E (likely referring to a-tocopherol) is associated with increased incidence of asthma and wheezing in children up to 5 years old (44,45). In Devereux's review of these data and changes in the environment in Scotland (45), it is discussed that from 1967 to 2004 there was a significant increase in vegetable oil intake by the Scottish, and we suggest that this would at least result in an increase in g-tocopherol, because vegetable oil (soybean oil) is rich in g-tocopherol ( Figure 1C).…”
contrasting
confidence: 47%
“…Thus, it is possible that in addition to increased ROS production, low TAC in children with AD may be due to low intake of dietary antioxidants, implicating dietary antioxidant intake with AD risk. Several previous studies have reported the beneficial association of dietary antioxidant vitamins with the risk of atopic diseases (39)(40)(41). For example, a higher concentration of vitamin C in breast milk is associated with a reduced risk of AD in infants (ORs0.30, 95% CI 0.09-0.94) (42).…”
Section: Discussionmentioning
confidence: 99%
“…The timing of assessment of maternal intake of antioxidants during pregnancy has not been uniform across studies. For instance, although some studies assessed dietary intake during the first and second trimester (Litonjua et al, 2006; HĂ„berg et al, 2009;Whitrow et al, 2009), others assessed during the second trimester only (Martindale et al, 2005;Devereux et al, 2006), still others asked about maternal dietary intake at anytime during pregnancy (Miyake et al, 2010a, b). Maternal diet, although assessed during the eighth month of pregnancy in our study, was aimed at reflecting the overall picture of maternal diet during the first 8 months of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a reduced risk of asthma and wheezing in the offspring with high maternal intake of vitamin E during pregnancy (Martindale et al, 2005;Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010a), whereas no association was observed regarding eczema (Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010b). Similar inconsistencies have been seen concerning maternal intake of zinc and the risk of allergic outcomes (Shahen et al, 2004;Martindale et al, 2005;Devereux et al, 2006;Litonjua et al, 2006;Miyake et al, 2010b). Umbilical cord selenium and iron has been associated with wheezing and eczema in children (Shahen et al, 2004).…”
Section: Introductionmentioning
confidence: 92%